Cyclophilins A, B, and C Role in Human T Lymphocytes Upon Inflammatory Conditions - Gegunde, Sandra; Alfonso, Amparo; Alvariño, Rebeca; Alonso, Eva; Botana, Luis M. (Frontiers in Immunology, 2021)
Cyclophilins (Cyps) are a group of peptidyl-prolyl cis/trans isomerases that play crucial roles in regulatory mechanisms of cellular physiology and pathology in several inflammatory conditions. Their receptor, CD147, also participates in the development and progression of the inflammatory response. Nevertheless, the main function of Cyps and their receptor are yet to be deciphered. The release of CypA and the expression of the CD147 receptor in activated T lymphocytes were already described, however, no data were available about other Cyps in these cells. Therefore, in the present work intra and extracellular CypA, B and C levels were measured upon inflammatory conditions. In this way, when T lymphocytes were activated by concanavalin A incubation, both intra and extracellular Cyps levels and the CD147 membrane receptor expression were augmented leading to cell migration towards circulating CypA and CypB chemoattractants. When CypA was modulated by natural and synthetic selective compounds, the inflammatory cascade was avoided including T cell migration. Our results strengthen the relationship between CypA, B and C, their receptor, and the inflammatory process in human T lymphocytes, associating CypC with these cells for the first time.